Effect of ultrasonic surface rolling process on the impact wear behavior of Inconel 690 alloy at 25 °C and 300 °C. (1st June 2022) - Yin, Meigui; Yin, Haiyan; Long, Jiangqi
Abstract: As an important nuclear power material, Inconel 690 alloy always need to suffer various harsh impact wear behaviors during its service period. Therefore, how to further enhance its surface wear resistance and objectively reveal its fretting wear mechanism under various conditions have vital scientific values for improving its service performance. This study first applies specific ultrasonic surface rolling process (USRP) to treat the Inconel 690 alloy surface with two and four times separately. And then a controllable impact kinetic energy wear test rig is used to comparative investigate the impact wear behaviors of as-received and USRP treated samples at 25 °C and 300 °C temperature. Results indicate that USRP can effectively improve the near surface Nano-hardness, residual compressive stress and other mechanical properties of Inconel 690 alloy, thereby increasing its impact wear resistance. The impact wear mechanism at 25 °C is plastic deformation causes fatigue spalling, and some adhesion wear are found at the 300 °C wear condition.